Investigating relationships between girls’ confidence in their ability to do and learn mathematics, their perceptions of their learning environment and achievement. - Quinn, Sharon Elizabeth (Curtin University, 2021)
In light of calls to increase girls’ participation in STEM subjects this study explored associations between female students’ confidence in their ability to do and learn mathematics, their perceptions of the learning environment and their achievement. The study also examined differences between students’ confidence and their perceptions of the learning environment based on group membership. The study supports the view that developing a favourable learning environment could improve girls’ confidence in learning and doing mathematics.